2020
DOI: 10.3390/pharmaceutics12020160
|View full text |Cite
|
Sign up to set email alerts
|

Long-Acting Paliperidone Parenteral Formulations Based on Polycaprolactone Nanoparticles; the Influence of Stabilizer and Chitosan on In Vitro Release, Protein Adsorption, and Cytotoxicity

Abstract: Long-acting preparations containing the antipsychotic paliperidone for intramuscular injection has drawn considerable attention to achieve harmless long-term treatment. This study aimed to develop paliperidone loaded polycaprolactone (PCL) nanoparticles and investigate the influence of PCL/drug ratio, stabilizer type, and chitosan coating on physicochemical properties, protein adsorption, and cellular toxicity. Results showed that chitosan coating produced enlarged particle sizes, shifted the surface charges f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Similar results were formerly observed by Elmowafy et al. ( 2020 ). It was previously reported that the molecular weight, structure, and conformation of surfactants play a crucial role in determining the surface charge carried by the formulated vesicles, even with nonionic surfactants that act through steric stabilization (Kovacevic et al., 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were formerly observed by Elmowafy et al. ( 2020 ). It was previously reported that the molecular weight, structure, and conformation of surfactants play a crucial role in determining the surface charge carried by the formulated vesicles, even with nonionic surfactants that act through steric stabilization (Kovacevic et al., 2011 ).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, it should be mentioned, that negatively or neutrally charged nanoparticles prefer to co-localize with lysosomes [ 190 ]. Moreover, due to this higher extent of internalization it has been investigated that the highly positively charged chitosan enhances the cytotoxicity of various drug-loaded nanoparticles against different types of human cancer cell lines [ 189 , 191 ].…”
Section: Chitosan-coated and Modified Chitosan Nanosystems Encapsumentioning
confidence: 99%
“…Olive oil spectrum showed strong band absorption peaks at 2920 cm −1 and 2854 cm −1 (revealing C–H stretching vibration of methylene and methyl groups respectively), 1741 cm −1 (revealing carbonyl double bond stretching vibration) [ 44 ]. Pluronic F127 spectrum exhibited at 2824 cm −1 (revealing C-H stretching), 1281 cm −1 and 1239 cm −1 (revealing the stretching of C–O–C bonds) and 1105 cm −1 , (revealing C-O stretching) [ 45 ]. In the spectra of F1 and F4, they presented similarly except for the appearance of new peaks in F4 spectrum at 2920 cm −1 and 1753 cm −1 correspond to the typical stretching vibrations of olive oil (dashed lines).…”
Section: Resultsmentioning
confidence: 99%